Transition Metal Salt Promoted, Green, and High‐Yield Synthesis of Silver Nanowires for Flexible Transparent Conductive Electrodes. Issue 44 (25th November 2021) - Sarisozen, Sema; Tertemiz, Necip A.; Arica, Tugce A.; Polat, Nahit; Kocabas, Coskun; Balci, Fadime M.; Balci, Sinan
Abstract: Silver nanowires (AgNWs) have attracted considerable interest from both academia and industry owing to their excellent electrical, optical, and chemical properties. For large‐scale synthesis of AgNWs, the polyol method involving ethylene glycol, a toxic alcohol, has been widely used. We herein report on a facile, green, high yield, transition metal salt promoted, open atmosphere method for the synthesis of high quality AgNWs in a glycerol‐water mixture. We have shown that transition metal salts have a strong influence on the morphology of AgNWs. Importantly, in the presence of copper(II) chloride, AgNWs with a high aspect ratio of around 400 (length, 36 μm; diameter, 90 nm) were obtained. Additionally, for the first time, we have demonstrated AgNWs based flexible transparent conductive electrodes (TCEs) on poly(sodium 4‐styrenesulfonate) (PSS) treated polyethylene terephthalate (PET) substrate with a sheet resistance of 34 Ω/sq and transmittance of 91 % at 550 nm. The PSS layer on the PET substrate generated a highly hydrophilic surface, which boosts interaction of AgNWs with the PET surface. We envision that our results would play a significant role both in the synthesis of AgNWs with high aspect ratio and also in designing new rigid and flexible TCEs having high transmittance and low sheet resistance for applications especially in printable solar cells, organic light emitting diodes, and high performance flexible electronics. Abstract : We report on a facile, green, high yield, transition metal salt promoted, open atmosphere method for the synthesis of high quality AgNWs in a glycerol‐water mixture. Additionally, we demonstrate AgNWs based flexible transparent conductive electrodes on poly(sodium 4‐styrenesulfonate) treated polyethylene terephthalate substrate with a sheet resistance of 34 Ω/sq and transmittance of 91 % at 550 nm. We envision that our results would play a significant role especially in printable solar cells, organic light emitting diodes, flexible and foldable electronics.